2020
DOI: 10.11114/ijce.v3i2.4931
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Teachers in Times of Change: The Job Demands- Resources Model and Teacher Burnout During the COVID-19 Pandemic

Abstract: Burnout in teachers has been broadly investigated, but no studies have investigated burnout in teachers during a pandemic. The current study is based on a survey of 1278 Canadian teachers and examined whether the Job Demands-Resources model was a useful lens for examining teacher burnout in this unprecedented context. Results supported the model in general terms in that most demands were most strongly correlated with the initial exhaustion stage of burnout. However, not all resources were most strongly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
125
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(167 citation statements)
references
References 21 publications
19
125
1
5
Order By: Relevance
“…First, in terms of personal resources such as efficacy (defined here as subjective perceptions of competence) for using effective strategies, managing behaviours, and engaging students (Tschannen-Moran & Hoy, 2001), our current research during the COVID-19 pandemic (Sokal, Eblie Trudel, & Babb, 2020a) showed that all three components of teaching efficacy were significantly and negatively correlated with exhaustion and depersonalization and were significantly, positively correlated with accomplishment in Canadian teachers--as expected based on pre-pandemic research. Likewise, all three components of attitudes toward change (thoughts, feelings, and behaviours) were significantly and negatively correlated with exhaustion and cynicism, and significantly and positively correlated with accomplishment in our initial Canadian sample.…”
Section: Three Expected Findings In Our Covid-19 and Teacher Burnout supporting
confidence: 69%
See 4 more Smart Citations
“…First, in terms of personal resources such as efficacy (defined here as subjective perceptions of competence) for using effective strategies, managing behaviours, and engaging students (Tschannen-Moran & Hoy, 2001), our current research during the COVID-19 pandemic (Sokal, Eblie Trudel, & Babb, 2020a) showed that all three components of teaching efficacy were significantly and negatively correlated with exhaustion and depersonalization and were significantly, positively correlated with accomplishment in Canadian teachers--as expected based on pre-pandemic research. Likewise, all three components of attitudes toward change (thoughts, feelings, and behaviours) were significantly and negatively correlated with exhaustion and cynicism, and significantly and positively correlated with accomplishment in our initial Canadian sample.…”
Section: Three Expected Findings In Our Covid-19 and Teacher Burnout supporting
confidence: 69%
“…Third, the survey that we conducted in Manitoba in September 2020 showed that the role of on-site school leadership was integral to support of the vast majority of Manitoba teachers (92.5% of those surveyed) during the pandemic, as expected based on pre-pandemic research (Eyal & Roth, 2011;Podalsky et al, 2016;Richardson et al, 2008;Urick, 2016). This finding echoed our national survey, which also showed the importance of school administrators as resources to teachers (Sokal, Eblie Trudel, & Babb, 2020a). However, for those who planned to leave the profession (7.5% of the Manitoban teachers who were surveyed), the influence of their school leadership was inconsequential.…”
Section: Three Expected Findings In Our Covid-19 and Teacher Burnout supporting
confidence: 66%
See 3 more Smart Citations